Comment goûter des vestiges antiques ? Le cas des amphores - DANIEL JACOBI (Metaichmio Publications, 2022)
All French archaeological museums exhibit numerous Gallo-Roman vestiges. As these collections are old and well known, one could assume that they are no longer the subject of debate or of scientific issues. According to the example of the Roman amphora, we will compare three forms of mediation: the amphora as a picturesque find of the collector, the amphora as a pedagogical object and, finally the amphora as a research theme still subject to scientific debate.